Perception and adoption by cassava farmers of the PlantVillage Nuru application disseminated in the agricultural environment of Côte d’Ivoire: a case study in the departments of Dabou, Bouaké, and Man - Adjéi, Ettien A.; Traoré, Kassoum; Sawadogo/Compaoré, Eveline Marie F. W.; Amoakon, William J-L.; Kouassi, Nazaire K.; Kouassi, Modeste K.; Pita, Justin S. (Frontiers in Agronomy, 2024)
In Côte d’Ivoire, cassava is the source of calories for about 26 million people and generates significant income for stakeholders in the value chain. However, its production is threatened by Cassava Mosaic Disease (CMD), which causes yield losses of up to 70%. This disease remains poorly known among farmers, who often adopt poor cultivation practices that serve to amplify its spread. To address this issue, the Regional Center of Excellence for transboundary plant pathogens Central and West African Virus Epidemiology (WAVE) introduced an innovate android based plant disease detection smart application called “PlantVillage Nuru” to help farmers recognize the disease through real-time diagnosis in cassava fields. The present study analyzes the perceptions and adoption rate of this application by farmers in the diagnosis of CMD within three departments of Côte d’Ivoire. Quantitative and qualitative data were collected from 152 farmers and agricultural technicians, using a questionnaire and interview guide in Dabou, Bouaké and Man. Data obtained were analyzed through descriptive statistics on SPSS and content analysis. A binary logit regression model was then used to identify the determinants of Nuru application adoption with Stata version 12.1. The study revealed an adoption rate of 45%, focused mainly on monitoring the phytosanitary status of cassava fields (98%), selecting healthy cuttings as planting materials (52%), and accessing agricultural advice (21%). The use of the Nuru application was strongly influenced (P<0.001) by the size of cassava field owned, respondents’ participation in WAVE cassava disease awareness activities, the use of family labor, and whether the respondents own or received a smartphone from WAVE. Gender, level of education, the contact with agricultural extension service and internet access, were also significant determinants (P<0.01) in the use of the application. Despite the constraints of smartphone unavailability (65%) and the complexity of using the application (41%) observed, Nuru was considered by farmers (100%) to be an essential and reliable training tool for detecting and managing CMD but did not appear to be needed on a sustained and regular basis. These findings suggest the need for categorization, follow-up, and sustained support to farmers to improve the adoption of agricultural technologies.